Aspidistra luochengensis (Asparagaceae), a new species from Guangxi, China - Pan, Bo; Qin, Ying; Lin, Chun-Rui (Phytotaxa, 2019)
Aspidistra louchengensis (Asparagaceae) is described and illustrated from limestone areas in northern Guangxi Zhuang Autonomous Region, China. It is similar to A. obconica C.R.Lin & Yan Liu with the perianth obconical campanulate, stamens inserted at upper third of perianth tube, but it can be clearly distinguished by leaf blade narrower and longer, perigone lobes longer (6–8 mm), adaxial densely papillose and scabrous, apex acuminate and outcurved, and stigma upper surface slightly concave. This new species is only known from Luocheng Mulao Autonomous County in Guangxi, China.